The spread of metal and metal production technology in the Far Northeast and Alaska over the second millennium BC to the first millennium AD. Issue 3 (27th May 2019) - Dyakonov, Viktor M.; Pestereva, Kunney A.; Stepanov, Alexander D.; Mason, Owen K.
ABSTRACT: Findings and traces of early metallurgical production in the Far Northeast of Asia and Alaska show that the spread of bronze and iron metallurgy took place mainly along the Lena River towards of the Far Northeast, as well as to Taimyr. Spread of metallurgical technology is confirmed by the casting mould for a burin or awl, which was discovered in Eastern Chukotka on the Amguema River. However, metals in Chukotka were obviously too rare to trade until the first millennium AD. An eastward decline in emphasis on metals is evidenced. Across the Bering Strait, into Alaska, iron appeared nearly two thousand years later than it existed within the the Far Northeast of Asia. Traces of metallurgy production were not found in Alaska. The spread of metals across Northeast Asia to Alaska indicates the existence of lasting and persistent connections between the Lena River Basin, the Far Northeast and Chukotka.